LB0002 RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED, MULTIPLE-DOSE, PHASE 2B STUDY TO DEMONSTRATE THE SAFETY AND EFFICACY OF TILDRAKIZUMAB, A HIGH-AFFINITY ANTI-INTERLEUKIN-23P19 MONOCLONAL ANTIBODY, IN PATIENTS WITH ACTIVE PSORIATIC ARTHRITIS. (June 2019) - Mease, Philip J; Chohan, Saima; Fructuoso, Ferran J García; Chou, Richard C; Nograles, Kristine E; Mendelsohn, Alan M; Luggen, Michael E
Abstract : Background: Tildrakizumab (TIL), a high-affinity anti–interleukin-23p19 monoclonal antibody, is approved for moderate-to-severe plaque psoriasis treatment and is under investigation for psoriatic arthritis (PsA). Objectives: To evaluate the 24-week efficacy and safety results from the randomised, double-blind, placebo-controlled, multiple-dose, phase 2b TIL study in patients with active PsA (NCT02980692 ). Methods: Patients with active PsA were randomised 1:1:1:1:1 to receive TIL (200 mg once every 4 weeks [Q4W] [n = 78], 200 mg every 12 weeks [Q12W] [n = 79], 100 mg Q12W [n = 77], 20 mg Q12W to week 24 [n = 78]), or placebo (PBO) Q4W to week 24 (n = 79). Stable concomitant methotrexate or leflunomide use was permitted but not mandated. The primary efficacy endpoint was the proportion of patients who achieved a 20% reduction from baseline in American College of Rheumatology response criteria (ACR20) at week 24. Other outcome measurements included proportion of patients achieving ACR50/70 response and Psoriasis Area and Severity Index (PASI) 75, PASI 90, and changes in swollen and tender joint count at week 24. Safety assessments included monitoring of treatment-emergent adverse events (TEAEs). Results: Of 500 patients screened, 391 patients met inclusion criteria (including =18 years old, PsA diagnosis with symptoms for 6 months, and =3 tender and =3 swollen joints). Demographics and baseline disease characteristics are shown in Table 1. There were significantly greater proportions of ACR20/50/70 and PASI 75/90 responders with TIL vs PBO at week 24, and in some cases differences in parameters were noted as early as week 8 (Figure 1 and Table 2). The most frequent TEAEs through week 24 included nasopharyngitis (pooled TIL arms: 5.4% [17/312]; PBO: 6.3% [5/79]); and diarrhoea (TIL: 1.3% [4/312]; PBO: 0). There were no reports of candidiasis, inflammatory bowel disease, major adverse cardiac events, or malignancy. No patients discontinued treatment due to TEAEs and no deaths were reported. Serious TEAEs occurred in 2.2% (7/312) of TIL-treated patients vs 2.5% (2/79) in PBO-treated patients. Conclusion: By week 24, TIL was significantly more efficacious than PBO in treatment of joint and skin manifestations of PsA. Furthermore, there was a clear separation between TIL and PBO as early as 8 weeks for ACR20 (TIL 200 mg Q4W and 100 mg) and 12 weeks for ACR50 (all TIL groups). Shortening the dosing interval from Q12W to Q4W for the 200-mg dose did not result in a measurable increase in skin or joint response scores. There was a low rate of TEAEs in the TIL-treated group. Acknowledgement: Editorial support by Marie-Louise Ricketts, PhD & Claire Daniele, PhD, of AlphaBioCom, King of Prussia, PA, funded by Sun Pharma. Disclosure of Interests: Philip J Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Leo, Eli Lilly, Merck, Novartis, Pfizer, Sun Pharmaceutical Industries, Inc., and UCB., Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Galapagos, Gilead, Janssen, Leo, Eli Lilly, Merck, Novartis, Pfizer, Sun Pharmaceutical Industries, Inc., and UCB., Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Genentech, Janssen, Leo, Merck, Novartis, Pfizer and UCB.., Saima Chohan: None declared, Ferran J García Fructuoso Grant/research support from: AbbVie, Gedeon Richter, Lilly, MedImmune, Nichi-Iko, Pfizer, Sanofi-Aventis, Takeda, and UCB., Consultant for: AbbVie, Gedeon Richter, Lilly, MedImmune, Nichi-Iko, Pfizer, Sanofi-Aventis, Takeda, and UCB., Speakers bureau: AbbVie, Gedeon Richter, Lilly, MedImmune, Nichi-Iko, Pfizer, Sanofi-Aventis, Takeda, and UCB., Richard C Chou Consultant for: Receives consultation fees from Sun Pharmaceutical Industries, Inc., Kristine E Nograles Shareholder of: Holds shares in Celgene Corporation and Cara Therapeutics, Employee of: Sun Pharmaceutical Industries, Inc, Alan M Mendelsohn Shareholder of: Holds individual shares in Johnson and Johnson, and as parts of retirement account/mutual funds, Employee of: Sun Pharmaceutical Industries, Inc, Michael E Luggen Grant/research support from: AbbVie; Amgen; Genentech; Eli Lilly; Nichi-Iko; Novartis; Pfizer; R-Pharm; and Sun Pharmaceutical Industries, Inc., Consultant for: AbbVie; Amgen; Genentech; Eli Lilly; Nichi-Iko; Novartis; Pfizer; R-Pharm; and Sun Pharmaceutical Industries, Inc., Speakers bureau: AbbVie; Amgen; Genentech; Eli Lilly; Nichi-Iko; Novartis; Pfizer; R-Pharm; and Sun Pharmaceutical Industries, Inc.